Religious Atmosphere and Spirit of Place at the Santa Maria Scala Coeli Monastery: Community Transition and the Continuity of Contemplative Space in Évora, Portugal - Maria Joao Castro (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2026)
This study examines how the contemplative atmosphere of the Santa Maria Scala Coeli Monastery in Évora, Portugal, has been sustained despite the transition of its resident religious community from the male Carthusian Order to a female contemplative community of the Servidoras do Senhor e da Virgem de Matará. The research aims to analyze how spatial enclosure, temporal discipline, and embedded religious memory contribute to the continuity of spirit of place within a monastic site undergoing institutional change. This study employs a qualitative approach using spatial phenomenology and a narrative-oriented design. Data were collected through field observation of the monastery’s spatial configuration, visual documentation of architectural and landscape elements, and documentary analysis of historical, architectural, and institutional sources. The findings show that the contemplative atmosphere of Scala Coeli is produced through three interrelated dimensions: the layered architecture of enclosure that regulates access and withdrawal, the repetitive temporal order of bells, liturgy, silence, and ascetic routine, and the persistence of spiritual memory within the built environment during and after community transition. The study also finds that the departure of the Carthusian monks in 2019 and the installation of a female religious community in 2022 did not automatically dissolve the contemplative character of the monastery. Instead, the atmosphere continues through the relative stability of its architectural structure, the sedimentation of religious practices in space, and the renewed operation of clausura. The implications of this study lie in its contribution to the study of religious architecture, sacred atmosphere, and lived religion, particularly in showing that the continuity of contemplative space may persist across institutional and gendered transitions. The originality of this research lies in its integration of architectural analysis, temporal discipline, and community transformation within a single narrative-phenomenological framework for interpreting the continuity of spirit of place in a monastic environment.